2007
DOI: 10.1200/jco.2007.25.18_suppl.7635
|View full text |Cite
|
Sign up to set email alerts
|

A double blind phase II study of BIBF 1,120 in patients suffering from relapsed advanced non-small cell lung cancer (NSCLC)

Abstract: 7635 Background: Vascular endothelial-(VEGF), platelet derived- (PDGF), and fibroblast growth factor (FGF) with their receptors compose critical cellular pathways controlling angiogenesis. BIBF 1120 is an oral potent triple angiokinase inhibitor targeting VEGFR, PDGFR, FGFR kinases. Methods: In this double blind multi-center trial, patients with an ECOG score of 0–2 with locally advanced or metastatic (stage IIIB/IV) relapsed NSCLC after failure of first or second line chemotherapy were randomly assigned to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The triple angiokinase inhibitory pattern in combination with good efficacy in vivo defines a unique pharmacological target profile of this compound class, with potential for improved efficacy in cancer treatment. Compound 3 (BIBF 1120) is currently being evaluated in phase III clinical trials in the treatment of nonsmall cell lung cancer 21 and is in clinical development for other tumor types. Since it was shown that 2 and 3 are also highly effective in an animal model of lung fibrosis, 22 clinical development of 3 in idiopathic pulmonary fibrosis was recently initiated.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…The triple angiokinase inhibitory pattern in combination with good efficacy in vivo defines a unique pharmacological target profile of this compound class, with potential for improved efficacy in cancer treatment. Compound 3 (BIBF 1120) is currently being evaluated in phase III clinical trials in the treatment of nonsmall cell lung cancer 21 and is in clinical development for other tumor types. Since it was shown that 2 and 3 are also highly effective in an animal model of lung fibrosis, 22 clinical development of 3 in idiopathic pulmonary fibrosis was recently initiated.…”
Section: T H I S C O N T E N T Imentioning
confidence: 99%
“…Major toxicities associated with single-agent BIBF 1120 are nausea, vomiting and diarrhea. Interestingly, this agent is not associated with hypertension or hand-foot syndrome, both of which are common with other antiangiogenic agents (Mross et al, 2005;Von Pawel et al, 2007).…”
Section: Antiangiogenic Agentsmentioning
confidence: 86%
“…Preliminary results from a randomized phase II study comparing two dosing schedules of BIBF 1120 (150 and 250 mg BID) in patients with previously treated NSCLC showed similar results between the two arms, with a stable disease rate of 48% and a median PFS of 2.9 months. The outcomes seemed slightly improved in patients with a PS of 0 or 1 compared with those in patients who had a PS of 2 (Von Pawel et al, 2007). Major toxicities associated with single-agent BIBF 1120 are nausea, vomiting and diarrhea.…”
Section: Antiangiogenic Agentsmentioning
confidence: 97%